Socio-demographic correlates of first dose of measles (MCV1) vaccination coverage in India - Basant Kumar Panda; Suyash Mishra; Niyi Awofeso (BMC, 2020)
Abstract Background Between 2010 and 2018, measles-related mortality had halved in India mainly with effective measles vaccination campaigns and widespread coverage across the states and population subgroups. Despite the commendable vaccination coverage, 2.9 million children in India missed the first dose of measles vaccine (MCV1) in 2017, and many of those vaccinated were not vaccinated at the recommended age (i.e. between 9 and 12 months). This study analyzed pattern and correlates of MCV1 coverage and MCV1 administration at recommended age among children aged 12-23 months in India. Methods We used the official data from the recent round of National Family Health Survey (NFHS-4), a nationally representative cross-sectional household survey in India conducted in 2015-16. Descriptive statistics and logistic regression analysis were applied to ascertain the influence of specified socio-demographic variables affecting measles vaccination coverage in India. Results The study revealed the distinct variations in coverage of MCV1 between the districts of India. There were also major challenges with age recommended vaccination, with about 15% of eligible children not vaccinated within the recommended age range, attributable to several socio-demographic factors. Significantly, antenatal care utilization of mothers strongly influenced MCV1 coverage and age recommended MCV1 coverage in India. The study also identified that children who missed MCV1 had one or more adverse health risks such as malnutrition, anemia and diarrhea disease. Conclusions A socio-economic gradient exists in India's MCV1 coverage, mediated by antenatal visits, education of mothers, and highlighted socio-demographic factors. Infection with measles was significantly correlated with greater anthropometric deficits among the study cohort, indicating a wider range of benefits from preventing measles infection. Eliminating morbidity and mortality from measles in India is feasible, although it will require efficient expanded program on immunization management, enhanced health literacy among mothers, continuing commitment from central state and district political authorities.